HEALTH RISK ASSESSMENT OF PESTICIDE EXPOSURE IN FARMERS AROUND RICE FARMING AREA IN OGAN ILIR REGENCY, SOUTH SUMATRA, INDONESIA - Maksuk; Intan Kumalasari; Maliha Amin; Pane, Masdalina (The Indonesian Journal of Public Health, 2024)
Introduction: Pesticides are chemical compounds that are toxic to the environment and humans. Approximately 89.8% of farmers in South Sumatra use chemical pesticides. Aims: This study aims to analyze the health risks due to pesticide exposure among farmers residing in rice farming areas. Methods: This study used an analytical observational design with a cross-sectional approach and was conducted in Pemulutan Subdistrict, Ogan Ilir Regency, from October 2020 to January 2021. The sample size consisted of 61 randomly selected respondents. Blood test samples were taken and examined at the Palembang Health Laboratory Center. The cholinesterase was examined using the DGKC colorimetric (KINETIC) method. Independent t-test and multiple linear regression test were used to analyze the data. Results: The results of the analysis showed that the average cholinesterase level in the blood serum of the farmers was 7628.40 U/L. This study also found that 83.6% of the farmers did not use complete and standard personal protective equipment. The variables that were significantly associated with cholinesterase levels in the blood of the farmers were age group and length of farming. Length of farming was identified as a predictor variable. Conclusion: Pesticides used by farmers in rice farming areas vary widely, ranging from slightly to extremely hazardous. Although the cholinesterase levels in farmers are in the normal range, they can increase over a long period of time. The length of farming is a predictor of cholesterol levels in farmers.